Feeding frequency, but not dietary water content, affects voluntary physical activity in young lean adult female cats - Godoy, M. R. C. de; Ochi, K.; Mateus, L. F. de Oliveira [UNESP]; Justino, A. C. C. de [UNESP]; Swanson, K. S. (Amer Soc Animal Science, 2015)
The objective of this study was to investigate whether increased dietary water content and feeding frequency increased voluntary physical activity of young, lean adult female cats. A replicated 4 x 4 Latin square design with a 2 x 2 factorial treatment arrangement (feeding frequency and water content) was used. The 4 treatments consisted of 1 meal daily dry pet food without added water (1D; 12% moisture as is), 1 meal daily dry pet food with added water (1W; 70% total water content), 4 meals daily dry pet food without added water (4D; 12% moisture as is), and 4 meals daily dry pet food with added water (4W; 70% total water content). Eight healthy adult, lean, intact, young, female domestic shorthair cats were used in this experiment. Voluntary physical activity was evaluated using Actical activity monitors placed on collars and worn around the cats'necks for the last 7 d of each experimental period of 14 d. Food anticipatory activity (FAA) was calculated based on 2 h prior to feeding periods and expressed as a percentage of total daily voluntary physical activity. Increased feeding frequency (4 vs. 1 meal daily) resulted in greater average daily activity (P = 0.0147), activity during the light period (P = 0.0023), and light: dark activity ratio (P = 0.0002). In contrast, physical activity during the dark period was not altered by feeding frequency (P > 0.05). Cats fed 4 meals daily had increased afternoon FAA (P = 0.0029) compared with cats fed once daily. Dietary water content did not affect any measure of voluntary physical activity. Increased feeding frequency is an effective strategy to increase the voluntary physical activity of cats. Thus, it may assist in the prevention and management of obesity.
Keywords: Feline; Meal frequency; Moisture content; Obesity